1998
DOI: 10.1021/jp9805959
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Modification of Polystyrene Surfaces by Low-Energy Polyatomic Ion Beams

Abstract: The chemical modification of polystyrene surfaces by low-energy (10-100 eV) SF 5 + , C 3 F 5 + , and SO 3 + ions was studied by X-ray photoelectron spectroscopy and two-laser ion trap mass spectrometry. The mechanism of fluorination was found to be dissimilar for SF 5 + and C 3 F 5 + ions in this energy range at fluences of 10 14 -10 16 ions/cm 2 . SF 5 + was found to induce fluorination of the polymer surface by grafting reactive F atoms upon dissociation at impact. SF n fragments were not found to be grafted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
69
0

Year Published

1999
1999
2004
2004

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(73 citation statements)
references
References 34 publications
4
69
0
Order By: Relevance
“…Surface etching yields are approximately the same for the two ions at 0.26 C atom/ion and 0.29 H atom/ion for C 3 F 5 + and 0.28 C atom/ion and 0.31 H atom/ion for CF 3 + . However, total F uptake and deposition yield are higher for CF 3 + than for C 3 higher velocity of the CF 3 + . However, the highest density of F occurs at a depth of 10-15 Å for both C 3 F 5 + and CF 3 + ion beams.…”
Section: Computational Detailsmentioning
confidence: 76%
See 3 more Smart Citations
“…Surface etching yields are approximately the same for the two ions at 0.26 C atom/ion and 0.29 H atom/ion for C 3 F 5 + and 0.28 C atom/ion and 0.31 H atom/ion for CF 3 + . However, total F uptake and deposition yield are higher for CF 3 + than for C 3 higher velocity of the CF 3 + . However, the highest density of F occurs at a depth of 10-15 Å for both C 3 F 5 + and CF 3 + ion beams.…”
Section: Computational Detailsmentioning
confidence: 76%
“…Specifically, the average penetration depths are 16.0 Å for both C and F atoms after C 3 F 5 + ion deposition and 15.9 and 15.2 Å for C and F, respectively, in the case of CF 3 + ion deposition. More F atoms chemically bond to the PS during CF 3 + ion deposition than during C 3 F 5 + ion deposition, as shown in Tables 3 and 4. In general, ions or ion fragments that form covalent bonds with the polymer substrate have smaller penetration depths than nonbonded, embedded species.…”
Section: Computational Detailsmentioning
confidence: 96%
See 2 more Smart Citations
“…Although early workers in the field of plasma polymerization identified ions as important film precursors [6], radical species are most often cited as polymerization building blocks. Recently, Hanley and coworker have shown that ion beams of hyperthermal ions can produce thin films and can be used to modify material interfaces [7,8,9]. The size and structure of the ions used (i.e., CF 3 ϩ vs. C 3 F 5 ϩ ) can strongly affect film composition, structure, and surface reactivity of the ion.…”
mentioning
confidence: 99%